2017
DOI: 10.1186/s12917-017-1036-1
|View full text |Cite
|
Sign up to set email alerts
|

Codon 141 polymorphisms of the ovine prion protein gene affect the phenotype of classical scrapie transmitted from goats to sheep

Abstract: BackgroundA study to investigate transmission of classical scrapie via goat milk was carried out in sheep: firstly, lambs were challenged orally with goat scrapie brain homogenate to confirm transmission of scrapie from goats to sheep. In the second study phase, milk from scrapie-infected goats was fed to lambs. Lambs were selected according to their prion protein gene (PRNP) genotype, which was either VRQ/VRQ or ARQ/ARQ, with or without additional polymorphisms at codon 141 (FF141, LF141 or LL141) of the ovin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Accumulation of PrP Sc in RAMALT was not observed in the biopsy samples from the remaining sheep or any of the goats. Observed transmission of classical scrapie from goat milk to sheep at 18 mpi was similar to previous observations even though sheep in the current study consumed approximately one-tenth the volume of goat milk that resulted in scrapie infection in a study by Konold and colleagues [ 16 , 17 , 47 ]. Animals in the current study were housed as groups (sheep separate from goats) and lateral transmission from ovine milk inoculated sheep to co-housed flock mates has been described previously [ 10 ].…”
Section: Resultssupporting
confidence: 90%
“…Accumulation of PrP Sc in RAMALT was not observed in the biopsy samples from the remaining sheep or any of the goats. Observed transmission of classical scrapie from goat milk to sheep at 18 mpi was similar to previous observations even though sheep in the current study consumed approximately one-tenth the volume of goat milk that resulted in scrapie infection in a study by Konold and colleagues [ 16 , 17 , 47 ]. Animals in the current study were housed as groups (sheep separate from goats) and lateral transmission from ovine milk inoculated sheep to co-housed flock mates has been described previously [ 10 ].…”
Section: Resultssupporting
confidence: 90%
“…CH1641 is an experimental scrapie strain that was originally isolated from a British scrapie case and propagated by serial transmission in sheep. Our results may suggest that serial intracerebral transmission in sheep led to positive selection of 19 K over 21 K in CH1641, given the neurotropism of 19 K and evidences that experimental transmission per se could mediate the emergence of CH1641-like properties in recipient sheep 46,57 . Interestingly, it has been shown that the PrP Sc type in natural CH1641-like isolates does not fully match experimental CH1641, but shows intermediate properties between classical scrapie and experimental CH1641 suggesting the co-existence of 19 K and 21 K in a mixture 27 .…”
Section: Investigation Of a Uk Goat Herd Suggests Ch1641 As A Hidden mentioning
confidence: 68%
“…60 Furthermore, codon 141 polymorphisms affect the phenotype of classical scrapie, including clinical presentation and molecular phenotypes. 95 At least 50 PRNP polymorphisms have been described in goat breeds, 1,36 but how they affect incubation times and susceptibility to classical scrapie is less defined than in sheep. Amino acid substitutions that may affect susceptibility to classical scrapie include G127 S, 57 I142 M, 56 N146S/D, 124 H154 R, 10,20,125,158 Q211 R, 10 and Q222 K. 2,10,158 The M142 polymorphism appears to prolong incubation period in experimental studies 56 but not confer resistance to classical scrapie.…”
Section: Role Of the Host Prion Protein Gene (Prnp)mentioning
confidence: 99%